von Hippel innovation - Jason Potts (Prometheus)
Round about 1940, a number of elements related to innovation processes were pulled together and organized as ‘Schumpeterian innovation’. The result was to provide framing and focus – a useful new paradigm – to guide further innovation-related research. Today, we have reached the same point with respect to a new collection of innovation phenomena, defined relatively recently, that together contribute to a fundamentally different innovation paradigm. This paper explains these components – many developed and empirically tested only within the last four decades – and describes the overall new paradigm to which they contribute. The paper argues that it is appropriate to name this new paradigm after the individual who first envisioned it and, together with many collaborators, gradually characterized and tested the components needed to develop and explain the functioning of ‘von Hippel innovation’.